2003
DOI: 10.1051/0004-6361:20030118
|View full text |Cite
|
Sign up to set email alerts
|

Intraday variability in compact extragalactic radio sources

Abstract: Abstract. We present the data from 11 observing campaigns (carried out between 1989 and 1999) at the Effelsberg 100 m radio telescope to study Intraday Variability in Active Galactic Nuclei. Most of these observations were performed in total power and linear polarization. We give summary tables, light curves, and structure functions from these data sets. Due to the large number of individual observations, only examples of the lightcurves will be presented here; the complete set of figures will be accessible o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
164
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 119 publications
(172 citation statements)
references
References 37 publications
6
164
1
1
Order By: Relevance
“…The complete data calibration procedure guarantees a high level of accuracy, on the order of 0.5%, in normal weather conditions. Following the scheme by Kraus et al (2003), some quantities were used to evaluate significance and amplitude of the variability, namely the reduced chi-square-test, the rms flux density over mean flux density (the so-called modulation index, m), and the 3σ relative variability amplitude Y, which is corrected for noise-bias, defined as Y = 3 m 2 − m 2 0 , where m 0 is the mean modulation index of all calibrators, describing the statistical measurement accuracy during the observation. In Table 1, we list the observational information and the results of the observations, in which the time scales are obtained from a structure function analysis (SF) as introduced in the next section.…”
Section: Observation and Data Reductionmentioning
confidence: 99%
“…The complete data calibration procedure guarantees a high level of accuracy, on the order of 0.5%, in normal weather conditions. Following the scheme by Kraus et al (2003), some quantities were used to evaluate significance and amplitude of the variability, namely the reduced chi-square-test, the rms flux density over mean flux density (the so-called modulation index, m), and the 3σ relative variability amplitude Y, which is corrected for noise-bias, defined as Y = 3 m 2 − m 2 0 , where m 0 is the mean modulation index of all calibrators, describing the statistical measurement accuracy during the observation. In Table 1, we list the observational information and the results of the observations, in which the time scales are obtained from a structure function analysis (SF) as introduced in the next section.…”
Section: Observation and Data Reductionmentioning
confidence: 99%
“…Radio flux-density observations of the BL Lac Object S5 1803+784 have been reported by Quirrenbach et al (1992Quirrenbach et al ( , 2000 and Kraus et al (2003). They show slow variability, i.e.…”
Section: Introductionmentioning
confidence: 76%
“…The blazar S5 1803+784 (z ≈ 0.68, Lawrence et al 1987;Stickel et al 1993) is an intraday variable source with rapid fluxdensity variations in the optical and radio regime (Wagner & Witzel 1995;Quirrenbach et al 1992Quirrenbach et al , 2000Kraus et al 2003) on timescales as short as 50 min in the optical (Wagner et al 1990). It has been observed and studied with different VLBI arrays at a range of different frequencies (e.g., Eckart et al 1986Eckart et al , 1987Witzel et al 1988;Charlot 1990;Strom & Biermann 1991;Fey et al 1996;Gabuzda 1999;Gabuzda & Cawthorne 2000;Gabuzda & Chernetskii 2003;Ros et al 2000Ros et al , 2001Britzen et al 2005aBritzen et al ,b, 2008).…”
Section: Application To 1803+784mentioning
confidence: 99%
“…During normal weather conditions, we find m 0 values of between 0.5% and 0.7%. A more thorough description of the data calibration procedure can be found in Kraus (1997), Marchili (2009), and references therein.…”
Section: Observation and Data Calibrationmentioning
confidence: 99%
“…The flat-spectrum radio source AO 0235+164 (z = 0.94) was found to show variability on IDV timescales more than once in the past (see, e.g., Kraus et al 1999);Senkbeil et al (2008) reported a likely extreme-scattering-event in AO 0235+164 in July 2005. The source was observed with the Urumqi radio telescope in 21 epochs between December 2006 and November 2009.…”
Section: Variability Characteristics Of Ao 0235+164mentioning
confidence: 99%